813 The added value of transthoracic three dimensional echocardiography in apical hypertrophic cardiomyopathy. (8th December 2021) - Rella, Valeria; Gavazzoni, Mara; Tomaselli, Michele; Oliverio, Giorgio; Volpato, Valentina; Crotti, Lia; Cecchi, Franco; Parati, Gianfranco; Badano, Luigi; Muraru, Denisa
Abstract: We present the case of a 73-year-old patient with a recent diagnosis of hypertrophic cardiomyopathy (HCM). He was asymptomatic and has no family history of sudden cardiac death (SCD), syncope or ventricular arrhythmias. An echocardiogram performed at the moment of diagnosis (2020), showed left ventricular (LV) asymmetric apical hypertrophy with maximal wall thickness of 21 mm. Cardiac magnetic resonance (CMR) confirmed LV apical hypertrophy with mid-ventricular obliteration, and late gadolinium enhancement in the apical segments, without wall motion abnormalities present at rest. According to 2014 ESC guidelines, his calculated risk score for sudden cardiac death was low (1.23% at 5 years). On 2021, a comprehensive transthoracic echocardiographic examination including advanced techniques (three-dimensional echo-3DE-, and two-dimensional speckle-tracking-2DSTE) was done as part of his routine follow-up in our cardiomyopathy outpatient clinic. The echo study showed an asymmetric pattern of LV hypertrophy with a maximal wall thickness of 21 mm at the level of the anterolateral apical segment, normal LV volumes (end-diastolic volume 55 mL/m 2 ) and ejection fraction (69%) by 3DE. LV longitudinal strain analysis by 2DSTE showed impaired LV myocardial deformation mainly at the apical LV segments (GLS = −13.6%). There was evidence of dynamic intracavitary obstruction (maximal gradient 32 mmHg at rest and raised to 52 mmHg during Valsalva manoeuvre). 3DE views of the LV (both multi-slice display and 3D rendered image) allowed to avoid foreshortening of the LV apical views, and to appreciate the actual wall motion at the real LV apex. They revealed a LV apical aneurysm which was not detected in the conventional LV-focused apical 2D views (Figure 1 A and B ). Apical hypertrophic cardiomyopathy (ApHCM) is a variant of HCM that is characteristic of focal thickening of the LV apical myocardium and was reported to have a more benign course than other non-apical forms. However, the presence of LV aneurysm in ApHCM patients is associated with an increased risk for ventricular arrhythmias, sudden cardiac death and thromboembolism. Accordingly, the detection of apical LV aneurysms has significant impact on patient management. Guidelines recommend the use of contrast echocardiography or CMR when the apical region of the LV is suboptimally visualized by conventional 2D echocardiography. However, contrast echocardiography may still be affected by apical foreshortening resulting in suboptimal accuracy, as it is a 2D technique. On the other end, CMR may be contraindicated or not widely available for routine yearly follow-up for all HCM patients requiring regular imaging follow-up. Our clinical case emphasizes the added value of 3DE to increase the sensitivity of transthoracic echocardiography in detecting apical LV aneurysms in patients with apical HCM with important clinical implications for the management of the patient.